Low-temperature acoustic-based activation of biochar for enhanced removal of heavy metals. (April 2020) - Sajjadi, Baharak; Chen, Wei-Yin; Mattern, Daniell L.; Hammer, Nathan; Dorris, Austin
Abstract: Conventional carbon activation requires heating carbon at a temperature greater than 700 °C for over 3 h, consuming 18, 600 kcal/kg of activated biochar. In contrast, the ultrasound treatment method is conducted at ambient condition for a very short duration (∼30 s, which requires about 1135 kcal/kg of activated BC produced. The advanced low-temperature acoustic-based surface modification method not only increases the porosity and surface functionality of raw biochar, but also is economically feasible and environmentally friendly. As a sequel of our previous works, this study aims to investigate the interaction between ultrasonic-structural modification with four different pre-treatments including i) control with no pretreatment, ii) EDC/HBOt, iii) alkali using KOH, iv) acid using HNO3 or H3 PO4 . The process was then followed by amine functionalization with DEA (diethanolamine) for nickel removal. The results demonstrated that all acoustic-based amine-functionalized biochar samples, without any exception, had more amine- and oxygen-containing functional groups as well as micro porosity, compared to those aminated without acoustic-activation, particularly in samples pretreated with HNO3 and H3 PO4 . Despite an increase in porosity by ultrasonication, metal leaching from US-only samples and those activated with EDC/HOBt was observed during longer adsorption durations. However, the synergism created by the combined effect of ultrasound and KOH and H3 PO4, not only enhanced the adsorption capacity of biochar but also significantly reduced the adsorption duration from 8 to 3 h. The highest nickel adsorptions were observed for ultrasonic-amine samples activated with H3 PO4 > HNO3 ∼ KOH, which were far higher (60 %, 49 %, and 46 % more adsorption, without any leaching) than raw or US-biochar, or biochar aminated with EDC/HOBt or without pretreatment.